The transcendence of displacement : precarious inquiries into the popular and the banal : an exegesis presented with exhibition as fulfillment of the requirements for thesis Master of Fine Arts at Massey University, Wellington, New Zealand - Bowen, James Lewis; Bowen, James Lewis (Massey University, 2011)
This dissertation investigates, through a body of interdisciplinary artwork, the discrepant relationships between the time-based and the static image. It examines how these two distinct states of the image interrogate time/image devices found on virtual platforms of participation and how it might be possible to exchange this dynamic with a contemporary art register. The five artworks operate as idiosyncratic inquires into heightening a precarious and affective relationship with the viewer/spectator and each artwork’s conception and response to popular imagery and subsequent iconography. By using this content to make perception-altering visual forms this content navigates a trajectory that challenges the primitive operation of nostalgia and perpetual objecthood. By bringing together seemingly unrelated discourses such as the Gothic, Shock and Queer aesthetics the artworks in this study attempt to call into doubt and subvert the postmodern traditions of appropriation and banality with immersive environments. This project has explored a lexicon of different mediums including video, cinematic readymades, photography and installation. This engagement with varying disciplines highlights an attempt to speculate how society adheres to a collective unconscious that is mediated through popular content, which simultaneously occupies the binary of virtual and physical space. An emphasis is placed on the space between this binary and creates a dialogue that extracts and exploits encoded formulas circulating in popular culture. By creating a series of dialogues between time-based and static imagery, physical and virtual spaces and fragmented signifiers of holistic narratives, this project aims to subvert the reality that chronicles iconic imagery and attempts to liquidate signatures of time by converging time-based and static mediums.
Keywords: Time-based art; Gothic art; Shock art; Queer art